5-Azacytidine mediated reactivation of silenced transgenes in potato (Solanum tuberosum) at the whole plant level - Tyč, Dimitrij; Nocarová, Eva; Sikorová, Lenka; Fischer, Lukáš (Plant cell reports, 2017)
Transient 5-azacytidine treatment of leaf explants from potato plants with transcriptionally silenced transgenes allows de novo regeneration of plants with restored transgene expression at the whole plant level. Transgenes introduced into plant genomes frequently become silenced either at the transcriptional or the posttranscriptional level. Transcriptional silencing is usually associated with DNA methylation in the promoter region. Treatments with inhibitors of maintenance DNA methylation were previously shown to allow reactivation of transcriptionally silenced transgenes in single cells or tissues, but not at the whole plant level. Here we analyzed the effect of DNA methylation inhibitor 5-azacytidine (AzaC) on the expression of two silenced reporter genes encoding green fluorescent protein (GFP) and neomycin phosphotransferase (NPTII) in potato plants. Whereas no obvious reactivation was observed in AzaC-treated stem cuttings, transient treatment of leaf segments with 10 μM AzaC and subsequent de novo regeneration of shoots on the selective medium with kanamycin resulted in the production of whole plants with clearly reactivated expression of previously silenced transgenes. Reactivation of nptII expression was accompanied by a decrease in cytosine methylation in the promoter region of the gene. Using the plants with reactivated GFP expression, we found that re-silencing of this transgene can be accidentally triggered by de novo regeneration. Thus, testing the incidence of transgene silencing during de novo regeneration could be a suitable procedure for negative selection of transgenic lines (insertion events) which have an inclination to be silenced. Based on our analysis of non-specific inhibitory effects of AzaC on growth of potato shoots in vitro, we estimated that AzaC half-life in the culture media is approximately 2 days.
Keywords: azacytidin; zelené fluorescenční proteiny; Reactivation; Solanum tuberosum; geneticky modifikované rostliny; Transgenes; Green Fluorescent Proteins; Transgene silencing; De novo regeneration; transgeny; regulace genové exprese u rostlin; Methylation; Gene Expression Regulation, Plant; Gene Silencing; DNA Methylation; metylace DNA; umlčování genů; Plants, Genetically Modified; 5-Azacytidine; TGS; Azacitidine